Friday

March 6, 2015

March 6, 2015

Posted by **Jen** on Sunday, October 15, 2006 at 11:05pm.

Please help. Thanks in advance.

We have x

Are there supposed to be 2 equal signs in this expression or is it

x

I'll suppose it's the second one.

You need to differentiate this implicitly to find dy/dx. Then find an equation for the normal line and set it equal to the curve.

The implicit derivative looks like

2x + 2x*dy/dx + 2y -6y*dy/dx = 0

Solve for dy/dx and use the negative reciprocal of dy/dx at the point (1,1) as the slope of the normal.

I'm not sure if you know what this second degree curve is, but it's an ellipse. The normal line at any point should intersect the ellipse in two points.

It appears your function is

x

This is not an ellipse, but a pair of lines that pass through the origin, at least according to what I got in my graphics application.

Differentitate this to get

2x + 2x*dy/dx + 2y = 6y*dy/dx so

2(x+y) = 2*dy/dx(3y -x) and

dy/dx = (x+y)/(3y -x)

At (1,1) dy/dx = 2/2 = 1 so the normal has slope = -1

The equation of the normal is

y-1 = -1(x-1) or

y = -x + 2

Check the points (1,1) and (3,-1)

Sorry it is x^2+2xy-3y^2=0

Thanks for the answers.

How did you get the point (3,-1)? Thanks.

Your function factors as (x-y)(x+3y)=0

These are the lines y=x and y=(-1/3)x

The point (1,1) is on the line y=x with slope 1. The normal has slope -1 and goes through that point. It intersects the other line at (3,-1).

(2x-y)(3y+x)

- Calculus -
**Erin**, Tuesday, June 18, 2013 at 10:53pmThis might help: You already know how to find the equation for the normal line is y=-x+2. Plug this equation into the original equation of the curve in place of y:

x^2+(2x)(-x+2)-(3)(-x+2)^2=0

x^2-2x^2+4x-3x^2+12x-12=0

-4x^2+16x-12=0

(-4)(x^2-4x+3)=0

x^2-4x+3=0

(x-1)(x-3)=0

Now we know that x=1 and x=3 are the only two places where the graphs can cross. We already know when x=1 then y=1, so we only need to pay attention to x=3. Plug x=3 into the line for the normal curve to determine the y-value at that point:

y=-x+2

y=-3+2

y=-1

So we know the second point is (3, -1). I posted this response so belatedly because I had a tough time figuring this out from the responses I found (here and on other sites), so I hope this helps other students who are struggling with the concept.

- Calculus -
**Mr. Wes**, Tuesday, October 7, 2014 at 7:02amAwesome!

**Answer this Question**

**Related Questions**

Derivatives - What is the fourth derivative of f(x)= e^-x^2. I got f''(x)=-2e^-x...

Calc, Implicit Differentiation - Regard y as independent variable and x as ...

Calculus - Use implicit differentiation to find the slope of the tangent line to...

Powers in Math - (5a^3b^4)^2=? *I don't get this one...PLease Help! (5a3b4)2= (5...

help - Y^3Y/Y^-2 If you post with the correct word in the Subject line, you'll ...

Property of logarithms - Using property of logarithms, how do I prove derivative...

math-volume - I'm confused with how to solve this problem, so help would be ...

calc - Where do I start to prove this identity: sinx/cosx= 1-cos2x/sin2x please ...

Chemistry - Sorry for posting this again, I dont know if the question was ...

Math - If a^3 = x^2 what is a^2y+1 = x^6, solving for y You would have (x2)3 = ...